The Macabre on the Margins: A Study of the Fantastic Terrors of the Fin de Siècle - Beville, Maria (Text Matters: A Journal of Literature, Theory and Culture, 2012)
With a view to discussing an important three-faceted example of marginality in literature whereby terror, the literary Fantastic and the fin de siècle period are understood as interconnected marginalia, this paper examines works such as Guy de Maupassant’s “Le Horla” and H. Rider Haggard’s She from an alternative critical perspective to that dominating current literary discourse.It demonstrates that in spite of the dominant associations of fantastic literature with horror, terror, as the marginal and marginalized fear of the unknown, with its uncanny, sublime and suspenseful qualities, holds a definitive presence in fin de siècle fantastic texts. Literary analysis of the chosen texts registers significant examples of the importance of terror to fantastic writing, and as such functions to extract an “aesthetics of sublime terror” from the margins of critical studies of this often macabre literary mode.